Rare-earth element doping-promoted toluene low-temperature combustion over mesostructured CuMCeOx (M = Y, Eu, Ho, and Sm) catalysts: the indispensable role of in situ generated oxygen vacancies. Issue 22 (26th October 2018) - Jiang, Zeyu; Chen, Changwei; Ma, Mudi; Guo, Zheng; Yu, Yanke; He, Chi
Abstract : The synergetic effect between Ho and the CuCeO x framework creates abundant active oxygen vacancies and significantly enhances the toluene destruction activity. Abstract : Novel CuMCeO x (M = Y, Eu, Ho, and Sm) trimetal oxide catalysts with developed mesoporosity and an enhanced oxygen migration capability were fabricated by a reproducible self-precipitation approach for the first time. The incorporation of a rare-earth element (especially Y, Eu, and Ho) can increase the reducibility of, and mobility of surface adsorbed oxygen on, a CuCeO x catalyst, which leads to a remarkable increase in catalytic activity in the oxidation of toluene. Among these catalysts, the CuHoCeO x catalyst possesses the highest oxidation activity, with the complete mineralization of toluene at 220 °C at a relatively high GHSV of 50 000 h −1, which is ascribable to the synergetic effect of Ho and the CuCeO x framework, which creates abundant active oxygen vacancies over mixed oxides. Raman spectroscopy and density functional theory (DFT) studies reveal that Ho element is coordinated to two oxygen atoms and occupies the site of a Ce atom, which changes the π-bonding of Ce in the CuCeO x binary oxide and thus leads to the weakening of Ce–O bonds and an enhanced oxygen storage capacity. A possible reaction pathway and a mechanism for the combustion of toluene over a CuHoCeO x sample are proposed by means of in situ DRIFTS and DFT studies, which prove that the toluene oxidation process obeys the Mars–van Krevelen mechanism, with aldehydes and ketones as the primary organic intermediates, before decomposition to CO2 and H2 O.